Star wars. the empire strikes back Episode V. - Lucas, George; Kurtz, Gary.; Twentieth Century-Fox Film Corporation; Lucasfilm, Ltd.; Twentieth Century Fox Home Entertainment, Inc. (Hollywood, Calif. Lucasfilm Ltd, 2000)
Luke Skywalker seeks out the mysterious jedi master Yoda while Han Solo and Princess Leia outrun the Imperial fleet en route to Cloud City.
Originally released as a motion picture in 1983.
Issued in a case with star wars, episode IV : a new hope ; episode VI : return of the jedi.
Director of photography, Gilbert Taylor; editors, Richard Chew . . [et al.]; music, John Williams.
Mark Hamill, Harrison Ford, Carrie Fisher, Billy Dee Williams, Anthony Daniels, David Prowse, Kenny Baker, Peter Mayhew, James Earl Jones, Frank Oz, Alec Guinness.
MPAA rating: PG.
VCD
Keywords: Skywalker, Luke -- (Fictitious character) -- Drama; Organa, Leia -- (Fictitious character) -- Drama; Solo, Han -- (Fictitious character) -- Drama; Vader, Darth -- (Fictitious character) -- Drama; Life on other planets -- Drama; Space warfare -- Drama; Good and evil -- Drama